December 1941 : twelve days that began a world war - Mawdsley, Evan, 1945- (Yale University Press, 2011)
In far-flung locations around the globe, an unparalleled sequence of international events took place between December 1 and December 12, 1941. In this riveting book, historian Evan Mawdsley explores how the story unfolded. He demonstrates how these dramatic events marked a turning point not only in the course of World War II but also in the direction of the entire century. On Monday, December 1, 1941, the Japanese government made its final decision to attack Britain and America. In the following days, the Red Army launched a counterthrust in Moscow while the Japanese bombed Pearl Harbor and invaded Malaya. By December 12, Hitler had declared war on the United States, the collapse of British forces in Malaya had begun, and Hitler had secretly laid out his policy of genocide. Churchill was leaving London to meet Roosevelt as Anthony Eden arrived in Russia to discuss the postwar world with Stalin. Combined, these occurrences brought about a "new war," as Churchill put it, with Japan and America deeply involved and Russia resurgent. This book, a truly international history, examines the momentous happenings of December 1941 from a variety of perspectives. It shows that their significance is clearly understood only when they are viewed together